100 Gb/s long‐reach WDM‐PON implemented by using directly modulated RSOA. Issue 6 (27th March 2013) - Tawade, Laxman
Abstract This article presents long reach wavelength division multiplexing passive optical network (WDM‐PON) system capable of delivering 100 Gb/s data to each subscriber. For cost‐effectiveness, WDM‐PON is implemented in loopback configuration using directly modulated reflective semiconductor optical amplifiers (RSOAs) at 25 Gb/s. We use four RSOAs at each optical network unit for the 100‐Gb/s upstream transmission. The operating wavelengths of these RSOAs are separated by the free‐spectral range of the cyclic arrayed waveguide gratings used at the central office and remote node (RN) for (de)multiplexing the WDM channels. We extend the maximum reach of this WDM‐PON to 123 km by using Erbium‐doped fiber amplifiers at the RN. The results show that the error‐free transmission can be achieved for all WDM channels in the wavelength range of >35 nm with sufficient power margins. Bit error rate and Q‐factor were measured to demonstrate the proposed scheme. In this article, long reach and large data service aspects of an access network are presented. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1426–1430, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27581 DOI 10.1002/mop.27572